Continuous quality improvement strategies in engineering curriculum - Ihsan, Sany Izan; Khalifa, Othman Omran (2011)
Engineering Education is facing new challenges to improve their outcomes toward higher quality to meet the job market demand and to keep abreast with current technologies. Continuous Quality Improvement (CQI) is the key that might provide accountability and essential ingredient in this quality improvement effort. It is an analytical decision making tool which allows the management to monitor the process of education whether it is working predictably or needs correction. This requires a CQI approach based on innovation, evidence, best practice and evaluation to better meet the needs. The strategies of continuous quality improvement are normally described in terms of ability to satisfy the current and future needs of industry, mobility, and life-long commitment to learning. In this paper, the need for continuous quality improvement in higher education; the role of academic in higher education; some of the strategies and techniques universities are employing for continuous quality improvement are discussed. The self-assessment methodology and the evaluation of system inputs, process and outcomes is highlighted. The relationship between CQI and the outcomes-based approach (OBA) is presented